Cause of climate change and issues in uttrakhand - Vikas Bhola (International Journal of Environmental Planning and Development Architecture, 2024)
Uttarakhand is experiencing a surge in average temperatures and a significant shift in precipitation regime, causing significant changes in the duration, amount, and form of atmospheric precipitation. The region's shorter snowfall season is believed to be responsible for decreased water supply, leading to water scarcity. The shift in plant blossoming and fruiting has also led to a shift in traditional life support activities, resulting in decreased agricultural productivity, increased pest infestations, and animal attacks. These changes are part of coping strategies for people experiencing climate-induced changes. The Himalayan region, particularly Uttarakhand, is vulnerable to frequent forest fires due to high summer temperatures, while infrastructure and croplands are severely affected by excessive rainfall. Unpredictable climatic variations in the mountains prompt residents to migrate towards the plains. This study analyzes extreme precipitation and temperature indices, focusing on landslides and forest fire incidents. The region has seen declining trends in soil water content, total precipitation, total run-off, and leaf area index (LAI). The rise in weather extremes over the last four decades poses challenges for both the community and government in adapting to these changes.
Keywords: Climate; Global; Rain fall; Snow fall; Weather; temperature